Ethnic/Racial Disparities in Longitudinal Neurocognitive Decline in People With HIV. (1st May 2022) - Wei-Ming Watson, Caitlin; Kamalyan, Lily; Tang, Bin; Hussain, Mariam A.; Cherner, Mariana; Rivera Mindt, Monica; Byrd, Desiree A.; Franklin, Donald R.; Collier, Ann C.; Clifford, David B.; Gelman, Benjamin; Morgello, Susan; et al.
Abstract : Background: To examine longitudinal neurocognitive decline among Latino, non-Latino Black, and non-Latino White people with HIV (PWH) and factors that may explain ethnic/racial disparities in neurocognitive decline. Methods: Four hundred ninety nine PWH (13.8% Latino, 42.7% Black, 43.5% White; baseline age: M = 43.5) from the CNS HIV Anti-Retroviral Therapy Effects Research (CHARTER) study completed neurocognitive, neuromedical, and laboratory assessments every 6–12 months with up to 5 years of follow-up. Longitudinal neurocognitive change was determined via published regression-based norms. Survival analyses investigated the relationship between ethnicity/race and neurocognitive change, and baseline and time-dependent variables that may explain ethnic/racial disparities in neurocognitive decline, including socio-demographic, HIV-disease, medical, psychiatric, and substance use characteristics. Results: In Cox proportional hazard models, hazard ratios for neurocognitive decline were increased for Latino compared with White PWH (HR = 2.25, 95% CI = 1.35 to 3.73, P = 0.002), and Latino compared with Black PWH (HR = 1.86, 95% CI = 1.14 to 3.04, P = 0.013), with no significant differences between Black and White PWH ( P = 0.40). Comorbidities, including cardiometabolic factors and more severe neurocognitive comorbidity classification, accounted for 33.6% of the excess hazard for Latino compared with White PWH, decreasing the hazard ratio associated with Latino ethnicity (HR = 1.83, 95% CI = 1.06 to 3.16, P = 0.03), but did not fully account for elevated risk of decline. Conclusions: Latino PWH may be at higher risk of early neurocognitive decline compared with Black and White PWH. Comorbidities accounted for some, but not all, of this increased risk among Latino PWH. Future research examining institutional, sociocultural, and biomedical factors, including structural discrimination and age-related biomarkers, may further explain the observed disparities.